Antecedents and consequences of work engagement among Thai employees - Chuchai Smithikrai (2020)
© Behavioral Science Research Institute. The purposes of this study were, 1) to identify antecedents and consequences of work engagement in the Thai context, and 2) to examine the patterns of relationships between these antecedents and consequences of work engagement. The present study propose three potential antecedents of work engagement: 1) positive orientation, 2) career satisfaction, and 3) attitude toward organization. It also propose that work engagement would be related to three positive work behaviors (i.e., proactive work behavior, innovative work behavior, and organizational citizenship behavior). The sample comprised of 608 employees working in public and private organizations in Thailand. As predicted, positive orientation, career satisfaction, and attitude toward organization are related to work engagement as its antecedents (γ = .31, .22, and .26, ps < .01). The results indicate that work engagement predicts proactive work behavior, innovative work behavior, and organizational citizenship behavior (β = .27, .22, and .17, ps < .01). In addition, work engagement partially mediates the relationship between these three antecedents and three types of positive work behaviors. The variances accounted for the partial mediations were between 16.4% and 37.3%. These findings offer implications for the management of human resources in organizations, including designing enriched jobs, providing a supportive work environment, and selecting candidates with positive-orientation towards job.